1995
DOI: 10.4038/jnsfsr.v23i1.5569
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific neighbour effects on the growth and morphological plasticity of Salvinia molesta

Abstract: The tropical fresh water fern salvinia(Sa1vinia mlesta D.S. Mitchell) ' is a problematic weed and is being controlled biologically by the introduction of a weevil, Cyrtobagous salviniae. The plant consists of three morphologically different growth forms; primary, secondary and tertiary, duringitsgrowth. The present paper describes how the initial density of primary stage plants affected its morphological plasticity. Primary stage apical cuttings consisting of three ramets (uniform in size) were selected and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The experiment showed that increasing density generally reduced branching of S. molesta . This result is consistent with the previous observations 12 , 13 , 16 , 19 .…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The experiment showed that increasing density generally reduced branching of S. molesta . This result is consistent with the previous observations 12 , 13 , 16 , 19 .…”
Section: Discussionsupporting
confidence: 94%
“…It has been commonly recognized that the following relationship is present between the growth forms (stages) and density 16 , 21 , 29 : primary growth stage (form A or B) occurs in adverse conditions or during the initial invading stage of the infestation and thus the population density is low; the secondary stage is found in open water (either freely or on the edge of stable mats); and the tertiary stage (form L) occurs only under higher density. It seems that population density or crowding condition is the primary cause of the growth stages (forms) in S. molesta .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The effect of density of plants on its morphological plasticity has also been studied. 16 In thick growing mats of S. molesta (i.e. at the tertiary stage) density stress is unavoidable.…”
Section: Introductionmentioning
confidence: 99%